POLISH SYSTEM OF CHILDREN AND YOUNG PEOPLE’S FOOTBALL TRAINING IN THE OPINION OF THE COACHES - Dariusz Mucha; Karol Görner; Robert Makuch; Adam Jurczak; Jože Štihec (Sport Scientific And Practical Aspects, 2025)
Strategic objective of young players’ training should be supplying league teams with comprehensively trained and motivated 18- year-old athletes. The main aim of the training process is to get "a complete, comprehensive player" predisposed in "senior age”, in order to achieve the masterly level. It is not obtaining current (ad hoc) results at any cost though. Without the connection of the theory with practice there are noreliable results in the longer term and, above all, the proper conduct of the player from the early period of being an abecedarian to an advanced senior level. The flywheel development of football is the training of children and young people according to the European and world standards.